THE URGENCY OF LEGAL PROTECTION TO THE WOMAN AND CHILDREN EXPLOITATION IN THE NEW BROADCASTER AND SOCIAL MEDIA - Sapto Budoyo (JOURNAL EQUITABLE, 2022)
The Development of technology and social media have an impact on the women and children matters in a public sphere. Verbal violence against women and children being a crucial matters in a social media and broadcast platform, therefore legal protection is needed for woman and children against those actions. This research consist of two points there are the urgency of legal protection for woman and children in exploitation and discrimination in the broadcast and social media in Indonesia. This research using normative legal methods with analytical descriptive based on library research. The result of this research shows that the urgency of legal protection needed on woman and children’s exploitation and discrimination in broadcast and social media platform due to Indonesia has ratified CEDAW through Law Number7 of 1984 concerning on the ratification of CEDAW. The implementation of legal protection on the woman and children’s exploitation and discrimination in Indonesia’s social media and broadcast platform has not been optimal. This problem due to the gap between enforcement officers, and society’s role with the prevention and handling children and women’s exploitation and discrimination cases in social media and broadcast platform.